Mid-Urethral Sling for Stress Incontinence: Does Urodynamic Pressure Reading Affect Post-Operative Outcome? - Abdullah A. Ghazi; Ali Alabbad; Malak Abuzgaya; Mai A. Banakhar; Dean S. Elterman; Sidney Radomski; Magdy Hassouna (Journal of King Abdulaziz University: Medical Sciences, 2019)
The aim of our study was to determine the effect of preoperative urodynamic reading of valsalva leak point pressure on the result of mid-urethral sling surgery. From January 2010 to December 2014, a total of 207 patients underwent mid-urethral sling surgery at the Toronto Western Hospital. An incontinence questionnaire was sent to 94 patients who accepted to be involved in the study to examine satisfaction post-surgery. Forty-five patients replied and were included in the analysis. The patients were divided into three groups according to valsalva leak point pressure (< 60, 60-80 and > 80 cm H2O) determined on urodynamic testing. Of the forty-five patients who responded to the questionnaire, seven were excluded for only having had stress testing done and two were excluded due to intermittent catheterization. Thirteen patients had evidence of detrusor overactivity on urodynamic testing. Simple linear regression analysis was done for the three groups of the valsalva leak point pressure values and correlation to satisfaction was found -0.263, -0.236, and -0.148, respectively. In this current study, we could not find a relation between valsalva leak point pressure values and the self-reported satisfaction post-surgical correction.